Pesticide Toxicity Profile: Triazine Pesticides: PI-121/PI158, 4/2006 - Fishel, Frederick M. (EDIS, 2006)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of triazine pesticides registered for use in Florida. This document is PI-121, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2006. PI-121/PI158: Pesticide Toxicity Profile: Triazine Pesticides (ufl.edu)